2005
DOI: 10.1097/01.med.0000152979.05456.b6
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal surgery and gut hormones

Abstract: Purpose of review Surgical treatment of obesity remains by far the most effective means of achieving weight loss, and in addition leads to normalised glucose tolerance in patients with type 2 diabetes mellitus (T2DM). Bariatric surgical procedures have recently been shown to effect changes in the secretion of gastro-intestinal hormones involved in energy regulation and intermediary metabolism that may contribute to appetite reduction, weight loss and remission of T2DM. Recent findingsGhrelin is released from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 103 publications
1
8
0
3
Order By: Relevance
“…These studies have recently been reviewed, and the heterogeneity of the findings makes it unlikely that ghrelin has a major role in the weight loss after RYGB. 46 In our study, compared with lean control subjects, both bypass and banding patients had lower fasting ghrelin levels, although these were similar to those of the obese control subjects. In agreement with the majority of studies, we did not find an anticipated compensatory rise in ghrelin among surgical subjects.…”
Section: Discussionsupporting
confidence: 52%
“…These studies have recently been reviewed, and the heterogeneity of the findings makes it unlikely that ghrelin has a major role in the weight loss after RYGB. 46 In our study, compared with lean control subjects, both bypass and banding patients had lower fasting ghrelin levels, although these were similar to those of the obese control subjects. In agreement with the majority of studies, we did not find an anticipated compensatory rise in ghrelin among surgical subjects.…”
Section: Discussionsupporting
confidence: 52%
“…Roux-en-y gastric bypass surgery has been associated with marked changes in gut peptide levels. For example, the majority of studies have shown that the orexigenic hormone ghrelin which is secreted from the stomach and preempts initiation of meals is reduced in the blood following gastric bypass [12,13]. Conversely, peptides such as peptide YY (PYY) and glucagon-like peptide 1 (GLP-1), which normally reduce food intake as well as stimulate insulin release and inhibit glucagon secretion when given to obese subjects, are elevated postprandially following gastric bypass consistent not only with an effect on reduced appetite but also with an amelioration of non-insulin-dependent diabetes mellitus [14].…”
Section: Introductionmentioning
confidence: 99%
“…The causes for reduced food tolerance may have different mechanisms. These bariatric operations can limit the consumption of specific types of foods that cannot be digested well (e.g., vegetables, red meat) [8], while some patients report a generalized satiety following bariatric operations [9][10][11][12].Those changes may be derived from distinct influences on the secretion of gastrointestinal peptides that are involved in the regulation of appetite and eating behavior [13,14]. The effect of purely restrictive procedures such as laparoscopic adjustable gastric banding (LAGB) or sleeve gastrectomy (SG), and malaborptive procedure such as biliopancreatic diversion with duodenal switch (BPD-DS) or other combined restrictive and malabsorptive procedures such as Roux-en-Y gastric bypass (RYGB), on weight loss, nutritional deficiencies, quality of life improvement, correction of co-morbidities, and complications has been well documented [2,3,15,16].…”
mentioning
confidence: 99%